华文教育组织与中华文化传承—以马来西亚华文独立中学为例 - 陈 添来; 黄 妙芸 (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2022)
摘要华文教育组织是以开展华文教育、传承中华文化为目的的统筹协调组织，其中包括华文学校。在海外，华文学校历来是传承中华文化的重要支柱，也是当地华族的文化堡垒。华文学校能够根据青少年儿童的年龄特征，系统地及循序渐进地进行母语母文化教育，因而能够最有效地传承中华优秀文化。马来西亚华文独立中学（简称独中）是由马来西亚民间华人社会所赞助、维持和创办的中学总称。华文独立中学的创办就是要肩负着发展中华民族母语教育和传承中华民族文化，培育民族子女，为国储才的教育任务。华文独立中学坚持以华文为主要教学媒介和使用华文教材，确立了华文中学是华文小学教育的延续，也是一贯的母语教育系统。文章按照组织文化的层次理论，以华文独立中学为研究对象，着重分析华文独立中学组织文化的内部结构与中华文化的传承关系。华文独立中学的组织文化的内部结构可分为物质层文化建设、行为层文化建设、制度层文化建设和精神层文化建设。通过分析各层的文化建设，可以窥探各层文化如何通过建设华文独立中学的组织文化来传承、传播中华文化。华文独立中学的组织文化建设与中华文化传承有着密切关系，可对“一带一路”建设中的民心相通产生促进作用。关键词：华文独立中学;传播中华文化;组织文化;文化建设;民心相通 AbstractThe Chinese Education Organization is a coordinating and coordinating organization forthe purpose of carrying out Chinese education and inheriting Chinese culture, including Chineseschools. Overseas, Chinese schools have always been an important pillar for the inheritance ofChinese culture and a cultural fortress for the local Chinese. Chinese schools can systematicallyand gradually carry out mother tongue and mother culture education according to the agecharacteristics of teenagers and children, so they can most effectively inherit the excellentChinese culture. Malaysian Chinese Independent Secondary School (referred to as theIndependent Secondary School) is the general name of the secondary schools sponsored,maintained and founded by the Malaysian civil Chinese society. The establishment of HuawenIndependent Middle School is to shoulder the educational task of developing the mother tongueeducation of the Chinese nation, inheriting the Chinese nation's culture, cultivating the childrenof the nation, and serving as the national reserve. Chinese independent secondary schools insiston using Chinese as the main teaching medium and using Chinese teaching materials,establishing that Chinese secondary schools are the continuation of Chinese primary educationand a consistent mother tongue education system. According to the hierarchy theory oforganizational culture, this paper takes Chinese independent middle school as the research object,and focuses on analyzing the internal structure of Chinese independent middle school'sorganizational culture and the inheritance relationship of Chinese culture. The internal structure of the organizational culture of Chinese independent middle school can be divided into materiallevel culture construction, behavior level culture construction, system level culture constructionand spiritual level culture construction. By analyzing the cultural construction of each layer, wecan see how each layer of culture inherits and spreads Chinese culture by building theorganizational culture of Chinese independent middle schools. The organizational cultureconstruction of Chinese independent middle schools is closely related to the inheritance ofChinese culture, which can promote the people-to-people bonds in the construction of the "Beltand Road".Keywords: Chinese independent middle school; dissemination of Chinese culture; organizationalculture; cultural construction; people-to-people bonds